Effect of Denosumab or Alendronate on Vascular Calcification: Secondary Analysis of SALTIRE2 Randomized Controlled Trial - Jolien Geers; Rong Bing; Tania A. Pawade; Mhairi K. Doris; Marwa Daghem; Alexander J. Fletcher; Audrey C. White; Laura Forsyth; Emily Evans; Jacek Kwieciński; Michelle C. Williams; Edwin J. R. van Beek; et al. (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease)
Background Patients with osteoporosis demonstrate increased vascular calcification but the effect of osteoporosis treatments on vascular calcification remains unclear. The present study aimed to examine whether coronary or aortic calcification are influenced by denosumab and alendronic acid treatment. Methods and Results In a double‐blind randomized controlled SALTIRE2 (Study Investigating the Effect of Drugs Used to Treat Osteoporosis on the Progression of Calcific Aortic Stenosis) trial, patients with aortic stenosis were randomized 2:1:2:1 to denosumab, placebo injection, alendronic acid, or placebo capsule. Participants underwent serial imaging with computed tomography and 18F‐sodium fluoride positron emission tomography for the assessment of vascular calcium burden and calcification activity, respectively. We report the prespecified secondary analyses of 24‐month change in coronary calcium score, and 12‐month changes in thoracic aorta calcium score, coronary and aortic 18F‐sodium fluoride activity. One hundred fifty patients with aortic stenosis (72±8 years; 21% female) were randomized to denosumab (n=49), alendronic acid (n=51), and placebo (injection n=25, capsule n=25). There were no differences in change in coronary calcium scores between placebo (16 [−64 to 148] Agatston units) and either denosumab (94 [0–212] Agatston units, P=0.24) or alendronic acid (34 [−62 to 134], P=0.99). There were no differences in change in thoracic aorta calcium scores between placebo (132 [22–512] Agatston units) and either denosumab (118 [11–340], P=0.75) or alendronic acid (116 [26–498] Agatston units, P=0.62). There were no differences in changes in coronary or aortic 18F‐sodium fluoride activity between treatment groups. Conclusions Neither alendronic acid nor denosumab are associated with changes in the activity or progression of coronary or aortic calcification. Osteoporosis treatments do not appear to have major impact on vascular calcification of atherosclerosis. registration https://www.clinicaltrials.gov; Unique identifier: NCT02132026.